Oriented molecular attachments through sol–gel chemistry for synthesis of ultrathin hydrated vanadium pentoxide nanosheets and their applications - Rui, Xianhong (2014)
Ultrathin single-crystalline V2O5·0.76H2O nanosheets with a thickness of 1.5–2.6 nm are prepared on the basis of molecular-level ‘oriented attachment’ through special sol–gel chemistry. The initial formation of 3–7 nm nanodiscs by confining the condensation reactions within the ab plane is critical to form nanosheets. As a proof-of-concept, these nanosheets exhibit good properties for hydrogen sensors and supercapacitors.